The study about Social Economy and Social Enterprise in the Czech Republic - Magdalena Hunčová (Central European Public Administration Review)
The Social Economy is a topic, which has been newly established in the Czech Republic during last two or three years, though social enterprises have been active here for a long time. This study aims to define the Social Economy and makes some typology of Social Enterprises and their activities according to the Czech experience and with regard to the general perception. Some figures and case studies form the Czech Republic are given to underpin this study and to indicate the trends of the development in here. The development of the civil society has gone in coherence to the development of the social economy. The structure of social enterprises has its specific feature in the Czech Republic, because of many self-governments enterprises providing welfare on its level on one hand, and only a few (social) co-operatives or other self-help mutual symmetries on the other hand. Participation on social care is developing and social economy seems to improve within the last two years.